7: How to remove, repair the threshing drum and grease chase bearings of a diesel-powered maize... - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
This video explains how a farmer can remove and repair the threshing drum and how to grease the chase bearings. Greasing the chase bearings is an important maintenance procedure because it prevents damaging of the machine easily. It prolongs the lifespan of the bearings and the machine as a whole. It facilitates easy threshing and enables the threshing drum to run smoothly. This video was developed with funding from USAID through the Africa RISING Ghana project which is led by the International Institute of Tropical Agriculture (IITA). The purpose of the video is not to instantly turn farmers into specialist technicians, but to empower them to be able to perform basic maintenance activities when they don't have access to technicians.